Effect of Pattern Formation of Prisoners in The Correctional Institutions of Recidive (Case Study in Class II B Correctional Institution of Majalengka) - Agus Yuliana Indra (Jurnal Daulat Hukum, 2018)
To implement the penal system for prisoners needed community participation both during development and acceptance of returned prisoners who have completed their criminal past. Commitments on at least can be a positive contribution to the process of coaching inmates who in turn can minimize the repetition of criminal acts. Connecting to the problems above who want revealed in this research is how development patterns inmates at Correctional Institution IIB of Majalengka classes and how the influence of development patterns against the repetition of crime (Recidive). The research is qualitative research in the form of descriptive analysis using sociological juridical approach. Types and sources of data used are primary data and secondary data. Data collected through the study of literature and interviews, while the juridical analysis using qualitative analysis. From the research we concluded that the pattern of development in the Penitentiary correctional IIB of Majalengka class represents the continuum of criminal law enforcement practice can not be separated from the development of general conception of the criminal prosecution. While the influence of development patterns prisoners against the repetition of criminal offenses (recidivism) on Prison Class IIB of Majalengka is still a lack of mental development also coaching skills to inmates that resulted in former inmates do not have the mental well and the skills needed to live her life outside of Prison Class IIB of Majalengka so the prisoner repeated his evil deeds.Keywords: Pattern Development, Prisoners, Recidive.